KESUKSESAN IMPLEMENTASI SIAKAD DI UNIVERSITAS ROYAL: INTEGRASI MODEL D&M, TAM, UTAUT, DAN HABIT - Hainur Rasyid; Raja Tama Andri Agus (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study examines the factors affecting the success of Academic Information System (SIAKAD) implementation at Royal University using an integrated theoretical framework of the DeLone & McLean IS Success Model, Technology Acceptance Model (TAM), and Unified Theory of Acceptance and Use of Technology (UTAUT). The primary contribution of this study is the empirical examination of the Habit construct from UTAUT, which has not been previously tested in the Indonesian SIAKAD context based on the literature reviewed. A quantitative cross-sectional approach was employed using two-stage Structural Equation Modeling (Anderson & Gerbing, 1988) with jamovi 2.6/SEMLj. Data were collected from 270 respondents via stratified random sampling from a population of 8,193 users. The measurement model demonstrated acceptable fit (χ²/df=2.87, RMSEA=0.083, CFI=0.938, TLI=0.928, SRMR=0.037). Results indicate that Habit (β=0.773, p<0.001) is the dominant predictor of Usage Intensity, Information Quality (β=0.996, p=0.006) is the only quality dimension that significantly predicts User Satisfaction, and User Satisfaction (β=0.756, p<0.001) is the strongest predictor of Net Benefits. The high R² values (UI=0.910; US=0.792; NB=0.877) confirm that in long-term mandatory information system environments, habitual usage patterns are more predictive than system quality dimensions in explaining usage intensity. Keywords: SIAKAD; DeLone & McLean; Habit; Structural Equation Modeling; Mandatory System   Abstrak: Penelitian ini mengkaji faktor-faktor yang mempengaruhi kesuksesan implementasi SIAKAD di Universitas Royal menggunakan kerangka terpadu DeLone & McLean IS Success Model, TAM, dan UTAUT. Kontribusi utama penelitian ini adalah pengujian konstruk Habit dari UTAUT yang belum pernah diuji secara empiris dalam konteks SIAKAD Indonesia berdasarkan kajian literatur yang dilakukan. Pendekatan kuantitatif cross-sectional diterapkan menggunakan Structural Equation Modeling dua tahap (Anderson & Gerbing, 1988) dengan jamovi 2.6/SEMLj. Data dikumpulkan dari 270 responden melalui stratified random sampling (N=8.193). Model CFA menunjukkan fit yang dapat diterima (χ²/df=2,87, RMSEA=0,083, CFI=0,938, TLI=0,928, SRMR=0,037). Hasil menunjukkan Habit (β=0,773, p<0,001) sebagai prediktor dominan Intensitas Penggunaan, Kualitas Informasi (β=0,996, p=0,006) sebagai satu-satunya dimensi kualitas yang secara signifikan memprediksi Kepuasan Pengguna, dan Kepuasan Pengguna (β=0,756, p<0,001) sebagai prediktor terkuat Manfaat Bersih. Nilai R² tinggi (UI=0,910; US=0,792; NB=0,877) mengkonfirmasi bahwa dalam lingkungan SI wajib jangka panjang, pola penggunaan habitual lebih prediktif dibandingkan dimensi kualitas sistem dalam menjelaskan intensitas penggunaan. Kata kunci: SIAKAD; DeLone & McLean; Habit; SEM; Sistem Wajib